The death of a disease : a history of the eradication of poliomyelitis - Seytre, Bernard; Shaffer, Mary (Rutgers University Press, 2005)
Annotation In 1988, the World Health Organization launched a campaign for global eradication of polio. The goal is closer than ever as fewer than 2,000 people died from the disease in 2002, down from approximately 350,000 in 1988. In this book, the authors tell the story of this crippling virus that has struck down healthy children for centuries.